2018
DOI: 10.1089/bfm.2017.0184
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Care Providers, Family, and Friends as Sources of Breastfeeding Support Beyond Infancy

Abstract: Family and PCP support is likely to be important for the growing proportion of U.S. mother-child dyads who are breastfeeding beyond 12 months. Many, but not all, women rated their child's PCP as supportive, and lack of support was a reason women reported for changing PCPs. Evidence-based interventions in primary care to support breastfeeding beyond infancy are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Prior research has highlighted that women who stop breastfeeding are often given incorrect advice by healthcare providers with limited evidence-based training and information, lack of clinical evidence-based reasoning, misconceptions, or incorrect assumptions [22][23][24]. It has also been reported that a healthcare provider's lack of understanding toward extended breastfeeding can harm the patient-provider relationship [17,25] resulting in early supplementation or abandonment of breastfeeding. An important strength of our study was the use of a questionnaire with adequate internal consistency to assess the basic competency of healthcare providers who care for breastfeeding mothers and infants.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has highlighted that women who stop breastfeeding are often given incorrect advice by healthcare providers with limited evidence-based training and information, lack of clinical evidence-based reasoning, misconceptions, or incorrect assumptions [22][23][24]. It has also been reported that a healthcare provider's lack of understanding toward extended breastfeeding can harm the patient-provider relationship [17,25] resulting in early supplementation or abandonment of breastfeeding. An important strength of our study was the use of a questionnaire with adequate internal consistency to assess the basic competency of healthcare providers who care for breastfeeding mothers and infants.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the family support provided, the special situation with mobility restriction and social isolation measures favoured that most of the women developed their breastfeeding experience separated from this support network, thus expressing its absence. This informal support network has been previously described by various authors as a complex network but, at the same time, with a potential impact on breastfeeding and with significant influence on breastfeeding initiation and maintenance in the short-and long-term, even favouring its extension beyond 6 months of life, after the mother is reinstated to her work environment [39][40][41]. Within the family environment, other female family members or the woman's partner are usually the figures that provide most of this support, with the findings of this research being similar [42][43][44].…”
Section: Discussionmentioning
confidence: 94%
“…Whether such support is influential on much longer duration breastfeeding (beyond 12 months) remains unknown, particularly for dyads who have successfully already reached the 12‐month milestone. We recently reported that only about half of United States women in the same sample analyzed in the present study discussed their decision to continue breastfeeding beyond 12 months with their child's primary care provider 19 . Other factors like support from family or peers or motivating aspects of breastfeeding like bonding that may be important to longer‐term breastfeeding also remain relatively unexplored.…”
Section: Introductionmentioning
confidence: 86%
“…We recently reported that only about half of United States women in the same sample analyzed in the present study discussed their decision to continue breastfeeding beyond 12 months with their child's primary care provider. 19 Other factors like support from family or peers or motivating aspects of breastfeeding like bonding that may be important to longer-term breastfeeding also remain relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%